Professionalizacija i kommercializacija v olimpijskom sporte (na materiale tennisa i legkoj atletiki) - Borisova, O.; Kozlova, E. (Science in Olympic Sport, 2017)
The article covers the history of development of tennis and track and field athletics, the role of governing bodies in the context of professionalization and commercialization of sport, and the modern system of competitions, which influences the preparation of athletes. The prize funds of the most prestigious tournaments and the earnings of some outstanding athletes are shown. The role of sports elites as a powerful factor in the development of sport and increase its income is emphasized. The issues of social protection of athletes, mechanisms of regulation of labour relations, and problems faced by athletes are examined. The influence of professionals of various profiles on athletes` training and participation in competitions is demonstrated. The role of training centres as a powerful stimulus for the development of sportsand creation of a competitive environment have been identified along with the changes in value orientations of athletes. The prospects of the development of sport in new socioeconomic conditions are outlined.